Comparison of Oropharyngeal Microbiota in Healthy Piglets and Piglets With Respiratory Disease - Wang, Qun; Cai, Rujian; Huang, Anni; Wang, Xiaoru; Qu, Wan; Shi, Lei; Li, Chunling; Yan, He (Frontiers in Microbiology, 2018)
Porcine respiratory disease (PRD) is responsible for severe economic losses in the swine industry worldwide. Our objective was to characterize the oropharyngeal microbiota of suckling piglets and compare the microbiota of healthy piglets and piglets with PRD. Oropharyngeal swabs were collected from healthy (Healthy_A, n=6; Healthy_B, n=4) and diseased (PRD_A, n=18; PRD_B, n=5) piglets at 2-3 weeks of age from two swine farms in Guangdong province, China. Total DNA was extracted from each sample and the V3-V4 hypervariable region of the 16S rRNA gene was ampliﬁed and sequenced using the Illumina MiSeq platform. No statistically significant differences were observed in bacterial diversity and richness between the healthy and PRD groups in the two farms except for Shannon index in farm A. Principal coordinate analysis (PCoA) showed structural segregation between diseased and healthy groups and between groups of different farms. Among all samples, the phyla Firmicutes, Proteobacteria, and Bacteroidetes were predominant. At the genus level, Streptococcus, Lactobacillus, and Actinobacillus were the core genera in the oropharynx of healthy piglets from the two farms. Significant differences in bacterial taxa were found when the microbiota was compared regarding the health status. In farm A, the percentages of Moraxella and Veillonella were higher in the PRD group, while only Porphyromonas was significantly increased in the PRD group in farm B (p < 0.05). Compared to PRD groups, statistically signiﬁcant predominance of Lactobacillus was observed in the healthy groups from both farms (p < 0.05). Our findings revealed that Moraxella, Veillonella, and Porphyromonas may play a potential role in PRD and Lactobacillus may have a protective role against respiratory diseases.